Quantifying temporal variations in species richness, diversity, similarity, and shared species of non-volant small mammals in UNIMAS forested areas - Mathew, Jenang. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Species richness, diversity, similarity and shared species are fundamental measurements of community and regional diversity. These quantifications underline many ecological models and conservation strategies. Specifically, species richness, species diversity, species similarity and shared species of non- volant small mammals in UNIMAS Forested Areas is reported here by comparing the different sampling periods which were conducted from 2003 to 2011. Species diversity and species richness were analysed using ACE, Chao2 and Jacknife estimators, while species similarity were analysed using pair-wise comparison among sites by similarity indices and shared species estimators, available in EstimateS Version 8.2. SPADE software was used in this study in order to compare the findings between the analyser on species richness, species diversity, species similarity, and shared species. Results showed a different similarity index yields different estimations based on their approaches respectively. Species richness was slowly increasing from 2003 to 2010 and remained unchanged from sampling period done in 2010 and 2011. Cluster analyses with MVSP showed that the dendrogram diagrams between 2010 and 2011 studies was higher in similarity. In term of species diversity, year 2010 obtained the highest diversity of non-volant small mammals in UNIMAS Forested Areas. The cumulative curve of the species collected did not reach the asymptote. It shows that the trapping-day was not sufficient to represent the overall small mammals' community in UNIMAS Forested Area. Therefore, more sampling effort will be needed to increase the capture rate. Based on the estimation by the estimators, some unseen species has not been discovered yet.